Investigation of maximum power point tracking (MPPT) for active cooling mono-crystalline photovoltaic panel using fuzzy logic controller - Nurul Afiqah, Zainal (2017)
Interest promotion of solar energy to perform an efficient standalone PV system to replace the used of gas and coal as the main demand in producing electricity. Due to the nonlinearity of solar radiation and temperature, it leads to inconsistency in electricity production from the PV panel. To achieve the maximum power point (MPP) of PV panel, fuzzy logic (FL) based constant voltage (CV) algorithm is applied to the system. The aim of this project is to develop an efficient standalone PV system with cooling system. This system is develop in both simulation and experimental. A model of PV panel is designed based PV mathematical modelling by using single cell diode model. The simulation is done to analyze PV panel characteristics especially in variation of temperature and irradiations. These characteristics are used for the inputs in 'developing the Fuzzy Logic (FL) controller. As to control and maintain the temperature of PV panel on its optimum level, a cooling system is developed into the system. The cooling system helps to increase the PV voltage output as well as the power produce. From the simulation, I-V and P-V characteristics of PV panel are obtained. The implementation of cooling system results in 3.09% and 1.96% of Vpv and VOUT percentage change increasing respectively when the PV temperature drop down to 17.71 % averagely. This clearly shows the Vpv produce depends on the PV temperature. By implementing FL based CV algorithm into this method, it makes the system more robust and reliable in terms of effectiveness and efficiency. In conclusion, a standalone PV system is successfully designed and analyzed in both simulation and experimental set up to determine the PV panel characteristics and increase the system performances. By implementing the cooling system for PV panel as well as using FL controller in tracking PV MPP enhanced the performances of PV system and reduces the problems that affect the power generation from PV panel.